Rapid Assessment of Refractive Error, Presbyopia, and Visual Impairment and Associated Quality of Life in Nampula, Mozambique. (May 2015) - Loughman, James; Nxele, Lindelwa L.; Faria, Cesar; Thompson, Stephen; Ramson, Prasidh; Chinanayi, Farai; Naidoo, Kovin S.
Introduction: Uncorrected refractive error is the leading cause of visual impairment worldwide and leads to an impaired quality of life. This study was designed to determine the prevalence of uncorrected refractive error and presbyopia, to assess spectacle coverage, and to evaluate visual health-related quality of life among persons aged 15–50 years old in Nampula, Mozambique. Methods: Participants were assessed using a validated rapid assessment of refractive error protocol, comprised of a demographic questionnaire, a standardized ophthalmic assessment to determine refractive status and spectacle coverage, and a modified vision-related quality of life questionnaire to assess the impact of uncorrected refractive error on participants' visual health status. Results: Among the 3, 453 respondents, visual impairment prevalence was 3.5% (95%, CI 2.7%–4.2%), with 65.8% of those visually impaired being 35 years of age and older. Uncorrected refractive error prevalence was 2.6% (95%, CI 2.1–3.2%), and was the primary cause of visual impairment among 64.5% of cases. The spectacle coverage for uncorrected refractive error was 0%. Presbyopia prevalence was higher, at 25.8% (95%, CI 12.0–30.5%), with only 2.2% spectacle coverage. Respondents with visual impairment demonstrated statistically significantly lower quality of life scores compared to those without visual problems ( p < 0.01). Implications for practitioners: The uncorrected refractive error problem and a distinct lack of spectacle coverage for refractive error and presbyopia indicate an urgent need for the development and delivery of a comprehensive refractive error service in the Nampula region of Mozambique.